The influence of Islam in the governance of the Malay Sultanate - Zakariya, Hafiz; Sulkafle, Mohamad Hazizie (2019)
This paper analyses one of the intellectual heritages of the Malay society in the corpus of law; the Ninety-nine Laws of Perak. Specifically, it discusses the influence of Islam in the Ninety-nine Laws of Perak, This led to the development of the governance (tatanegara) of the Perak Sultanate. The functional approach of the anthropological study of law is adopted as the framework for this study. Accordingly, law is regarded as “the means by which conflicts and disputes are resolved in a given society” and as “a system that operates in conjunction with other systems to regulate and control the social order”. This study also provides anecdotes recorded in several historical accounts to prove the influence of this set of laws in the administration of the Perak Sultanate. It also emphasizes that for a fair assessment of the traditional Malay laws,